1998
DOI: 10.1007/bf03012220
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral oxygénation during prostaglandin E1 induced hypotension

Abstract: Purpose: To evaluate the cerebral oxygenation effects of hypotension induced by prostaglandin E t(PGEI) during fentanyl-oxygen anaesthesia. Methods: Ten patients who underwent elective cardiac surgery received infusion of PGE I . After measuring the baseline arterial, mixed venous and internal jugular vein blood gases, systemic haemodynamics, and regional cerebral oxygen saturation (rSO2) estimated by INVOS 3100 R, PGE, was continuously infused at 0.25-0.65 ~g'kg -*'min -t (mean dosage: 410 -+ 41.4 mg'kg -* -m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The effect of induced hypotension on cerebral blood flow and oxygenation has been investigated using Doppler ultrasonography 47,49,50,85 , infrared spectroscopy 82 , thermal gradient blood flow meter 6 , measurement of difference in oxygen content in arterial and venous blood samples 60,72 , clearance of intra-arterially injected xenon 133 60 and electroencephalography 82,179,186 . Most studies showed no decrease in cerebral blood flow during hypotensive anaesthesia 4-6,8, 23,24,50,82,85,94,107,116,131,142,163,181,184,186,199 and even if there were a statistically significant reduction there was no evidence of a long-term adverse outcome clinically. One study entered in the final review showed no significant difference in cognitive test scores between patients receiving normotensive and hypotensive anaesthesia 153 .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of induced hypotension on cerebral blood flow and oxygenation has been investigated using Doppler ultrasonography 47,49,50,85 , infrared spectroscopy 82 , thermal gradient blood flow meter 6 , measurement of difference in oxygen content in arterial and venous blood samples 60,72 , clearance of intra-arterially injected xenon 133 60 and electroencephalography 82,179,186 . Most studies showed no decrease in cerebral blood flow during hypotensive anaesthesia 4-6,8, 23,24,50,82,85,94,107,116,131,142,163,181,184,186,199 and even if there were a statistically significant reduction there was no evidence of a long-term adverse outcome clinically. One study entered in the final review showed no significant difference in cognitive test scores between patients receiving normotensive and hypotensive anaesthesia 153 .…”
Section: Discussionmentioning
confidence: 99%
“…Drug doses were chosen based on the literature 6,12-13 and on previous clinical experience. [14][15] The identities of the study drugs were unknown to all persons present at the ECT session. The data obtained during this study were analyzed later by an individual who was also unaware of treatment regimens.…”
Section: Methodsmentioning
confidence: 99%
“…Nineteen patients (15 boys and four girls) ranging in age from 6 to 18 years (12.8 ± 3.5 years) and in weight from 25 to 70 kg (46.7 ± 13.8 kg) were enrolled in the study. The surgical procedures included anterior chest wall thoracoplasty (8), anterior spinal fusion (7), and femoral osteotomy (4). There were a total of 268 readings obtained from the cerebral oximeter.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated the correlation of NIRS with cerebral tissue oxygenation or other measures of cerebral oxygenation such as jugular bulb venous oxygen saturation (4–8). Kim et al compared the correlation of NIRS and arterial oxygen saturation with jugular bulb venous oxygen saturation in 42 adult volunteers during hypoxemia (6).…”
Section: Discussionmentioning
confidence: 99%